1990
DOI: 10.1002/ange.19901020323
|View full text |Cite
|
Sign up to set email alerts
|

[4+2]‐Cycloadditionen von Phosphinodiazoalkanen: Synthese von 1,2,4λ5‐Diazaphosphininen

Abstract: Zu Partnern für [4 + 2]‐Cycloadditionen werden Diazoalkane durch einen Phosphinosubstituenten am Diazokohlenstoffatom. Dies zeigen die Umsetzungen von 1, R = OMe, Ph, mit 2, R′ = OMe, Ph, zu den Diaza‐λ5‐phosphininen 3. Mit tBuCP dagegen reagieren die Diazoverbindungen 1 in „normaler”︁ [3 + 2]‐Cycloaddition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 10 publications
2
1
0
1
Order By: Relevance
“…The diphosphanylketenimine (PPh 2 ) 2 CCNPh ( 3 ) and its mono‐oxidized form (OPPh 2 )(PPh 2 )CCNPh ( 8 ) behave as 1,3‐dipoles towards a variety of dipolarophiles such as alkynes, isocyanates and isothiocyanates, through formal [3+2] and [3+3] cycloaddition reactions involving the phosphanyl residues, allowing the synthesis of remarkable five‐ and six‐membered phosphaheterocycles. Thus, it can be concluded that the presence of the phosphanyl substituents considerably modify the reactivity of 3 and 8 when compared with classical organic ketenimines, in agreement with that already observed by Regitz et al4 and Bertrand et al1 for other phosphanyl substituted organic functionalities.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The diphosphanylketenimine (PPh 2 ) 2 CCNPh ( 3 ) and its mono‐oxidized form (OPPh 2 )(PPh 2 )CCNPh ( 8 ) behave as 1,3‐dipoles towards a variety of dipolarophiles such as alkynes, isocyanates and isothiocyanates, through formal [3+2] and [3+3] cycloaddition reactions involving the phosphanyl residues, allowing the synthesis of remarkable five‐ and six‐membered phosphaheterocycles. Thus, it can be concluded that the presence of the phosphanyl substituents considerably modify the reactivity of 3 and 8 when compared with classical organic ketenimines, in agreement with that already observed by Regitz et al4 and Bertrand et al1 for other phosphanyl substituted organic functionalities.…”
Section: Resultssupporting
confidence: 90%
“…In line with all of the above, and with other reported cycloaddition reactions of alkynes with phosphanyl‐substituted dipoles,1, 4, 12, 13 a mechanism for the formation of 5 a , b is proposed in Scheme . First, nucleophilic attack of a phosphorus atom of 3 at the electron‐poor alkyne followed by a 1,5‐electrocyclization affords 4a , b .…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…B. die Chlordiazirine (31) in uberschussigem Phosphaalkin (4). so findet [2+ 1)-Cycloaddition der thermisch erzeugten Carbenc an die P/C-Dreifachbindung zu den I-Phosphirenen (33) aktion, bei der sich der Ubergang von h'din k7a"-Phosphor durch eine markante Hochfeldverschiebung (6 = +315 bzw.…”
Section: Und 2-phosphireneunclassified